2021
DOI: 10.2106/jbjs.rvw.21.00006
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts in the Management of Advanced Trigger Finger

Abstract: While the majority of patients with trigger finger obtain excellent outcomes from nonoperative treatment or release of the A1 pulley, a subset of patients with advanced trigger finger, defined as trigger finger with loss of active or passive range of motion, may have incomplete symptom relief and warrant specific attention.» Advanced trigger finger is more refractory to complete symptom resolution from corticosteroid injection, and particular attention should be paid to incomplete improvement of flexion contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Previous studies have consistently reported excellent outcomes after OTFR, 22 also for individuals with DM. 11–21 However, these studies have not stratified for the type of DM, that is, T1D or T2D, and because both pathophysiology and complications 13 are different in the two types of DM, it is an important distinction.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies have consistently reported excellent outcomes after OTFR, 22 also for individuals with DM. 11–21 However, these studies have not stratified for the type of DM, that is, T1D or T2D, and because both pathophysiology and complications 13 are different in the two types of DM, it is an important distinction.…”
Section: Discussionmentioning
confidence: 77%
“…Operative management is reserved for cases that do not respond. 1 In this case report, we describe an anomalous attachment of the lumbrical muscle to the A1 pulley, which we determined was the cause of our patient's triggering.…”
mentioning
confidence: 77%
“…We believe that sharing our case may help raise awareness to possible anomalies such as that described in this case report. n Ayman Khoury, MD, MHA 1 Gil Gannot, MD 1 Amir Oron, MD 1…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis may require clinical and ultrasound evaluation. Initial management of trigger finger is conservative and involves non-steroidal anti-inflammatory drugs, metacarpophalangeal joint immobilization, and corticosteroid injections (99). If non-operative treatments are unsuccessful, then surgery is recommended (99).…”
Section: Fibrous Histiocytomamentioning
confidence: 99%